The Use of English on Instagram Captions: A Case Study in Camera Indonesia Photography Community - Tutut Nani Prihatmi; Rini Anjarwati; Puji Rahayu (EDUTEC : Journal of Education And Technology, 2021)
Along with Instagram's growing popularity as the primary medium for sharing photos and videos, the world of photography is also expanding at a rapid pace. The Instagram caption is always dropped every time people upload on social media. Photo captions often act as a result of critical thinking and a way to communicate ideas. This study used a qualitative descriptive approach to collect and describe information about using English caption on Instagram photos from the perspectives of Camera Indonesia photography community members: frequency, the purpose for dropping captions in English, its effect on their photo works, and how they view English captions on others people’ photo captions. Using 10 members as the respondents, the study found that writing caption in English acts mostly as self-expression and has not yet been done on a daily basis as the respondents do not habituate reading English materials.